IMPLEMENTASI SYARIAH ENTERPRISE THEORY PADA PROGRAM CORPORATE SOCIAL RESPONSIBILITY DI BPRS AL-MADINAH TASIKMALAYA - Amelia, Ade; Suryanto, Asep; Marlina, Lina (JURNAL EKONOMI SYARIAH, 2022)
Corporate Social Responsibility is one of the Indonesian government's programs to be able to build a more prosperous society. The government has high hopes with this program, the Corporate Social Responsibility program is expected to be able to help protect the environment, especially the area where the company stands. Of course, so that the program can run well and be on target, the management of the Corporate Social Responsibility program must be carried out properly, especially in terms of distribution of Corporate Social Responsibility funds which have been budgeted for by each company, especially Islamic banking. The data was taken based on internal data sources of BPRS Al-Madinah Tasikmalaya and also the results of interviews with CSR fund managers at BPRS Al-Madinah Tasikmalaya.Â The method used in this study is a descriptive method with a qualitative approach. With two data sources, namely primary data sources consisting of employees and secondary data sources consisting of supporting documents, working papers and photos obtained from the field. The data collection techniques used were interviews, observation and documentation. With the research instrument, the researcher himself is the main instrument in the study, observation guidelines and interview guidelines.The results of this study are that the Al-Madinah BPRS is sufficient to meet the criteria for disclosure of social responsibility reports when viewed based on Sharia Enterprise Theory, although there are still those who do not meet Sharia Enterprise Theory such as the absence of distribution of CSR funds for the environment. However, in reporting CSR funds for the Al-Madinah BPRS community, it meets the criteria for Sharia Enterprise Theory, because in its distribution, the Al-Madinah BPRS Tasikmalaya prioritizes CSR funds to be distributed to the surrounding community.